2005
DOI: 10.1111/j.1523-1755.2005.00682.x
|View full text |Cite
|
Sign up to set email alerts
|

Biventricular diastolic dysfunction in patients with autosomal-dominant polycystic kidney disease

Abstract: Both hypertensive and normotensive patients with ADPKD show significant biventricular diastolic dysfunction, suggesting cardiac involvement very early in the course of ADPKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
31
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 39 publications
(28 reference statements)
3
31
0
1
Order By: Relevance
“…[2] Increased left ventricular mass indexes, biventricular diastolic dysfunction, ED, increased carotid intima-media thickness, and exaggerated blood pressure response during exercise have been reported even in young normotensive patients with ADPKD with well-preserved renal function. [4,[14][15][16][17][18][19][20][21] Ambulatory blood pressure and non-dipping pattern have been shown to be more closely associated with target organ damage and a worsened cardiovascular outcome than clinic blood pressure in patients with essential hypertension. [22] Li Kam Wa et al [8] have reported that hypertensive patients with ADPKD have significantly less nocturnal fall in blood pressure compared to patients with essential hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Increased left ventricular mass indexes, biventricular diastolic dysfunction, ED, increased carotid intima-media thickness, and exaggerated blood pressure response during exercise have been reported even in young normotensive patients with ADPKD with well-preserved renal function. [4,[14][15][16][17][18][19][20][21] Ambulatory blood pressure and non-dipping pattern have been shown to be more closely associated with target organ damage and a worsened cardiovascular outcome than clinic blood pressure in patients with essential hypertension. [22] Li Kam Wa et al [8] have reported that hypertensive patients with ADPKD have significantly less nocturnal fall in blood pressure compared to patients with essential hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension in ADPKD is characterized by relative activation of the reninangiotensin-aldosterone system (RAAS) (20 -22), the sympathetic nervous system (23), endothelin (24), and vasopressin (25,26). Abnormalities in endothelial function, left and right ventricular function, and kidney blood flow are present before loss of kidney function and the development of hypertension, and renal excretion of sodium is reduced early in ADPKD (27)(28)(29)(30)(31)(32)(33)(34)(35). These observations suggest that defects as a result of mutations in the polycystins may result in a vascular phenotype that is specific to ADPKD.…”
mentioning
confidence: 99%
“…The RAS activation plays an important role in atherosclerosis, LVH heart failure, and end stage renal failure. 14,16 Hereditary factors and myocardial collagen matrix failure as well as RAS activation are the factors blamed for LVH etiology in normotensive polycystic kidney patients. 14,17 In the study by Valero et al 14 the contribution of ambulatory BP change to LVH in normotensive polycystic kidney patients was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 In a study, compared to control group, 23% higher LVH was identified in normotensive polycystic kidney patients. 16 One of the mechanisms highlighted that ischemia occurs as a result of cyst pressure to nearby tissues because of expansion. The RAS activation starts at early stages of the disease before hypertension and renal damage are seen.…”
Section: Discussionmentioning
confidence: 99%